Energy Poverty in Europe: A Multidimensional Approach - Bollino, Carlo Andrea; Botti, Fabrizio (PSL Quarterly Review, 2017)
With the European Commission’s “Third Energy Package”, the challenges posed by energy poverty have been recently acknowledged by European legislation. The paper develops a synthetic indicator of energy poverty for the purpose of assessing households’ well-being across different domains of inequality in access to energy services and to a healthy domestic environment. These dimensions are broadly defined in terms of energy affordability and thermal efficiency, two of the main manifestations of energy poverty. The analysis focuses on Europe and expands on existing economic literature by employing a fuzzy analysis for the definition of a multidimensional energy poverty index, which is then used to investigate the role of individual and household characteristics in shaping energy poverty. We find that during the European crisis energy poverty has been more stable than monetary poverty, and that thermal efficiency plays a crucial role in shaping individual and countries’ average degrees of energy poverty. JEL codes: I32; Q41; D10; D63